The Battle of Hastings, A Cartographic Narrative. Issue 1 (2nd January 2022) - Hewitt, Christopher Macdonald
Abstract : The Battle of Hastings (1066) is one of the most widely studied battles in medieval history. Yet despite the importance that research shows geography to play in the outcome of such conflicts, academic studies on the battle have yet to provide a researched-based cartographic analysis of the battle. This study, consequently, seeks to map the battle to scale to examine the size and impact of geographic factors in understanding the events that shaped the battle. The analysis was undertaken using a geographic information system (GIS) with qualitative and quantitative techniques. Historical and current data were combined in a series of detailed state of the art maps to bring an entirely new perspective to the nearly millennium long literature on the battle. Factors considered in the study included previous interpretations of battlefields, literary GIS, cartographic depictions of units and a cartographic narrative of the battle. Among the findings of this study were a firm demonstration of the importance of cartographic-based analysis in understanding the size of a medieval battlefield and the development of a literary military account.